L'Arte per tutti. Artistry e creatività nella formazione per tutta la vita - Antonella Coppi (Firenze University Press, 2019)
In Italian schools, we often attend meetings of artists with the teacher, especially because in kindergarten and primary schools, the tendency is to assign to a "specialist" the curricular and extra-curricular activities of visual expression, theatre, music, drama and choreography: those activities are considered to be too specific to be taught by a teacher considered a "generalist". This work offers a reflection on the role and identity of the artist-teacher in Italy today, to identify the critical urgencies, the relationship with institutions, limits and potential. Today, all these issues go beyond a single disciplinary field to address a broader concept of culture and, inevitably, of the human being. Mouving from a reflection on the need to develop more carefully the creative experiences in the formal contexts of our country, this contribution aims to offer a first approach to the roles and identities of the artist-teacher in Italy today, to identify the critical urgency, the relationship with institutions, limits and potential.